Can BODIPY Dimers Act as Photosensitizers in Photodynamic Therapy? A Theoretical Prediction - Alberto, Marta Erminia; De Simone, Bruna Clara; Russo, Nino; Sicilia, Emilia; Toscano, Marirosa (Frontiers in Physics, 2018)
The photophysical properties of some monomeric and dimeric BODIPY systems were investigated at the density functional theory level and herein reported. In particular, the absorption spectra were fully characterized, low energy singlet and triplet excited states were discussed also focusing on the energy difference gaps between them and computing the spin-orbit couplings values for the possible intersystem crossing channels. The heavy atom effect of iodine substituents on the photophysical properties of a monomer and on a dimer under investigation was also estimated. Results obtained on the considered compounds allow us to predict which is the most promising candidate to be suggested as a photosensitizer in photodynamic therapy.